Hermeneutika kontekstual: Sebuah dialektika sudut pandang penafsir dan teks dalam memahami kitab suci - Salmon Pamantung (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
Many Christians say that to derive meaning from the biblical text, we must let the text “speak” to us. The underlying assumption is that an interpreter must derive the “original” meaning of the text; he must not insert his thoughts (prejudices and context) into the text. Development studies and hermeneutics have produced many methods and approaches to address questions related to interpretation. I argue that there is always a dialectic between the interpreter and the text being read in the hermeneutical process. Based on the thoughts of Hans-Georg Gadamer, I propose a contextual hermeneutic model, which emphasizes the role of the interpreter's point of view in finding the meaning of the text. Using the descriptive-analytical method on various literatures, it is found that hermeneutics is always an interaction between the context of the biblical text and the current context, so the social, political, and cultural “lenses” into the filter cannot be avoided and ignored. We must realize that the “lens” used is only one of many, and contextual hermeneutics starts from that awareness. Therefore, contextual hermeneutics means an attempt to understand the text that considers the interpreter's point of view. Abstrak Banyak orang Kristen yang mengatakan bahwa untuk mendapat-kan makna dari teks Alkitab, kita harus membiarkan teks yang